2015
DOI: 10.1007/s00586-015-3996-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of single level disc prolapse treated with transforaminal steroid versus epidural steroid versus caudal steroids

Abstract: In current study, transforaminal steroid injection group has better symptomatic improvement for both short and long term as compared to interlaminar and caudal steroid injection group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 18 publications
2
40
0
1
Order By: Relevance
“…Four of the nine studies [26,28,31,32] performed patient blinding, and all trials demonstrated assessor blinding, with the exception of one study [32]. Regarding other bias, two studies [21,28] had been unclear. Four observational studies were assessed using NOS ( Table 3).…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Four of the nine studies [26,28,31,32] performed patient blinding, and all trials demonstrated assessor blinding, with the exception of one study [32]. Regarding other bias, two studies [21,28] had been unclear. Four observational studies were assessed using NOS ( Table 3).…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 93%
“…The method of concealment of allocation was reported in four studies [24,26,28,31]. Four of the nine studies [26,28,31,32] performed patient blinding, and all trials demonstrated assessor blinding, with the exception of one study [32]. Regarding other bias, two studies [21,28] had been unclear.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 95%
See 3 more Smart Citations